SYSTEMATIC LITERATURE REVIEW: PROBLEM SOLVING ABILITY REVIEWED FROM STUDENTS' LEARNING INDEPENDENCE - Ditasari, Dwi Dian; Sukestiyarno, Sukestiyarno; Kharisudin, Iqbal (Prima: Jurnal Pendidikan Matematika, 2025)
Mathematical problem solving ability is a process carried out by students to solve problems given by using their knowledge and understanding. From several facts obtained, mathematical problem solving ability in Indonesia is included in the low category. One of the factors causing the lack of students' problem solving ability is the lack of student learning independence so that students are not trained when they get non-routine questions given by the teacher. The purpose of this study was to determine the mathematical problem solving ability in terms of student learning independence. The research method used is the Systematic Literature Review (SLR) which is carried out by reviewing, evaluating, and interpreting various relevant studies. The results of the study stated that there is a very strong influence of learning independence on students' mathematics KPM. The higher the student's learning independence, the higher the student's mathematical problem solving ability.